RASIONALISME DALAM TAFSIR AHKAM: Rationalism in Legal Exegesis (Tafsīr Aḥkām) - Jaenudin, Jaenudin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2017)
Abstract Interpretation of al-Quran is a human effort to understand the meaning and purpose of Godâ€™s words based on their ability level. Various methods of interpretation have been born along with the development of religion and science. The method used in this study is Descriptive-Analysis by describing the method of interpretation. The verses of al-Quran in the field of Law have become a particular study, called as Tafsir Ahkam. In Islamic law, this study broadly branched out into rationalist schools of fiqh (ahl al-Ra'y) and textual Hijaz schools (ahl al-hadis). But these divisions are getting thinner as law development (instibath) requires reasoning gained from qiyas and istihsan or maslahat. Â Therefore, the tafsir ahkam method developed with the growth of the school of fiqh, and the emergence of a rational approach in tafsir ahkam is a logical consequence of a dynamic of ijtihad fiqh method development. Keywords: Tafsir, Ahl raâ€™yi, Fiqh. Â Abstrak Tafsir Al-Quran merupakan upaya manusia untuk memahami makna dan maksud firman Allah sesuai dengan kadar kemampuannya. Berbagai metode Tafsir telah lahir seiring dengan perkembangan ilmu agama dan sains. Ayat-ayat al-Quran di bidang Hukum telah menjadi bidang kajian tafsir tersendiri dan melahirkan tafsir ahkam. Metode yang dipergunakan dalam penelitian ini adalah Deskriptif-Analisis dengan menguraikan tentang metode penafsiran. Di bidang hukum Islam telah berkembang pula mazhab fiqh yang secara garis besar terbagi atas mazhab fiqh irak yang rasionalis (ahl al-Raâ€™y) dan mazhab Hijaz yang tekstual (ahl al-hadis). Namun ciri tersebut semakin tipis seiring berkembang istinbath hukum yang memerlukan penalaran baik dengan qiyas, istihsan atau maslahat. Karena itu, corak tafsir ahkam berkembang dengan tumbuhnya mazhab fiqh, dan lahirnya pendekatan rasional dalam tafsir ahkam sebagai konsekuensi logis dari pertumuhan metode ijtihad fiqh yang dinamis. Kata Kunci:Â Tafsir, Ahl raâ€™yi, Fiqh.